2012
DOI: 10.1021/sb300060e
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Circuits in Salmonella typhimurium

Abstract: Synthetic biology has rapidly progressed over the past decade and is now positioned to impact important problems in health and energy. In the clinical arena, the field has thus far focused primarily on the use of bacteria and bacteriophages to overexpress therapeutic gene products. The next generation of multigene circuits will control the triggering, amplitude, and duration of therapeutic activity in vivo. This will require a host organism that is easy to genetically modify, leverages existing successful circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…S. typhimurium is an excellent strain for clinical synthetic biology for cancer therapy since it is similar to E. coli, specifically colonizes tumors, and has been shown safe in human clinical trials 6,12,14,22 . Additionally, recent studies have found that many published circuits function in S. typhimurium without modification 24 . Using the experimental platform described here, we recently described how dynamic in vivo expression profiles can be programmed using the inherent instability of plasmid vectors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…S. typhimurium is an excellent strain for clinical synthetic biology for cancer therapy since it is similar to E. coli, specifically colonizes tumors, and has been shown safe in human clinical trials 6,12,14,22 . Additionally, recent studies have found that many published circuits function in S. typhimurium without modification 24 . Using the experimental platform described here, we recently described how dynamic in vivo expression profiles can be programmed using the inherent instability of plasmid vectors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the natural macrophage-homing mechanism of Salmonella has been used to introduce antigenic peptides to immune cells for prophylactic purposes, and for the delivery of ribozymes designed to inhibit macrophage-specific viral infections, such as cytomegalovirus [94][95][96][97]. The employment of attenuated Salmonella in vaccine delivery has promising commercialization potential and is currently the basis of several clinical trials [98,99].…”
Section: Synthetic Probiotics As Living Therapeuticsmentioning
confidence: 99%
“…This disparity is an illustration of host context dependence (18): a circuit may work in one host and work differently or not at all in another, often without clear reason. This issue is extremely important as we move beyond E. coli toward the programming of other microbes (19). A promising solution described by Egbert et al is to explicitly build tuning knobs into the circuits and adjust them to compensate for host-specific differences.…”
Section: Tuning Knobs For Genetic Circuitsmentioning
confidence: 99%